PENILAIAN KINERJA KEUANGAN PT. BANK MUAMALAT INDONESIA, TBK DENGAN METODE ECONOMIC VALUE ADDED - Iman, Fathia Ahya Nur; Widodo, Arry (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
The purpose of this study to determine the financial performance with the use of the EVA method to the assessment of the performance of PT Bank Mualamat Indonesia Tbk in the period 2010 - 2014. The research method used is quantitative descriptive method using Economic Value Added (EVA), which is an analytical method for evaluating the performance a company to take measurements of the profits (value) economically produced by the company during the period (period of time) specific. The results show the value of Bank Muamalat EVA is negative, meaning that Bank Muamalat in the year 20102014 can not create value-added enterprise or net operating profit after taxes (NOPAT) produced by the company is not able to finance or cover all capital costs or expenses incurred. In 2014 the value of EVA Bank Muamalat increasing, although still negative.